Forced marriage as a lived experience: victims’ voices - Villacampa, Carolina (International review of victimology, 2020)
The official response to forced marriage in the majority of European countries has been to criminalise the practice. Based on racial stereotypes and outdated Orientalist perspectives, this overlooks the prior need for appropriate empirical analysis in order to better understand the reality of the practice being regulated, and fails to provide victims with the means of protection they need beyond the framework of criminal law. Devising a suitable and effective strategy to address this form of victimisation instead requires an in-depth understanding of the effects that victims of these practices endure, and of what the victims themselves would consider best practice in terms of assistance and protection. In view of these primary objectives, after the existence of forced marriages in Spain had been demonstrated by the corresponding quantitative research, a qualitative research study followed, which was conducted through interviews with victims of forced marriage. The results are presented here. The secondary aim of the study was to draw up the basic guidelines for an integrated programme of action to address this process of victimisation.